2015
DOI: 10.1371/journal.pone.0120912
|View full text |Cite
|
Sign up to set email alerts
|

High Peripheral Blood Th17 Percent Associated with Poor Lung Function in Cystic Fibrosis

Abstract: People with cystic fibrosis (CF) have been reported to make lung T cell responses that are biased towards T helper (Th) 2 or Th17. We hypothesized that CF-related T cell regulatory defects could be detected by analyzing CD4+ lymphocyte subsets in peripheral blood. Peripheral blood mononuclear cells from 42 CF patients (6 months–53 years old) and 78 healthy controls (2–61 years old) were analyzed for Th1 (IFN-γ+), Th2 (IL-4+), Th17 (IL-17+), Treg (FOXP3+), IL-10+ and TGF-β+ CD4+ cells. We observed higher propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
(39 reference statements)
4
27
0
Order By: Relevance
“…The murine studies are also difficult to interpret given that Cftr‐ deficient mice do not develop spontaneous lung disease, in contrast to larger animal models such as the CF pig or ferret; hence, these larger animal models may be required to better understand the role of IL‐17 in CF lung inflammation. Consistent with the notion that Th17 cells contribute to disease, it has been reported that high circulating Th17 responses are strongly associated with poorer lung function . Conditional deletion of IL‐17RA or IL‐17RC in the conducting airway of mice attenuates IL‐17‐mediated neutrophil recruitment into the lung, demonstrating that airway epithelium is a key target of IL‐17RA/RC signaling .…”
Section: Interleukin‐17 and Cf Lung Diseasementioning
confidence: 53%
“…The murine studies are also difficult to interpret given that Cftr‐ deficient mice do not develop spontaneous lung disease, in contrast to larger animal models such as the CF pig or ferret; hence, these larger animal models may be required to better understand the role of IL‐17 in CF lung inflammation. Consistent with the notion that Th17 cells contribute to disease, it has been reported that high circulating Th17 responses are strongly associated with poorer lung function . Conditional deletion of IL‐17RA or IL‐17RC in the conducting airway of mice attenuates IL‐17‐mediated neutrophil recruitment into the lung, demonstrating that airway epithelium is a key target of IL‐17RA/RC signaling .…”
Section: Interleukin‐17 and Cf Lung Diseasementioning
confidence: 53%
“…Th17 cells, neutrophils and NKT cells are found in abundance in all-cause bronchiectasis compared to healthy controls [92]. While high Th17 infiltrates independently associate with poorer lung function in CF [93], activation of Th17 antigen-specific pathways have been described in non-CF bronchiectasis [94]. IL-17, a central mediator of the Th17 pathway lacks correlation with bronchiectasis disease phenotypes suggestive of the more prominent role that neutrophil-mediated inflammation likely plays in the pathogenesis of bronchiectasis [94].…”
Section: Immunology and Inflammationmentioning
confidence: 98%
“…The primary cause of morbidity and mortality in cystic fibrosis (CF) is destruction of lung tissue, in which the immune system plays a major role. We and others have shown dysregulation of adaptive CD4 + T cells in CF. However, although innate immune cells and their interactions with adaptive immune responses are clearly important in immune dysregulation in CF, there is little information available about the peripheral changes in innate immune cells other than neutrophils.…”
Section: Introductionmentioning
confidence: 62%